THE URGENCY OF REROOTING THE SHAME IN THE LIVES OF INDONESIAN POLITICIANS: An Ethical Philosophical Analysis - Karwayu, Andreas; Karwayu , Andreas (Universitas Katolik Parahyangan, 2025)
Shame is often ignored in Indonesian political discourse even though it is important in controlling the practical morality of politics and building public trust. Through library research methods, this article explores the relationship between shame, ethics and contemporary Indonesian political praxis. The view of this article is that shame, as an ability among various aspects of human emotion that shapes human behavior, has disappeared from the lives of Indonesian politicians. Shame, as a moral catalyst and also embedded in national culture, is ignored in the lives of politicians. This is proven by various forms of unethical behavior in Indonesian political life, which ultimately harms Indonesia's rational and moral democratic order. Indonesia's political landscape is now filled with intrigue, ambition and dishonesty, manifesting in corruption, collusion, nepotism, patronage, policies that are detrimental to the people and oligarchic spirit. Based on various sources of ethical theory and political phenomena in Indonesia, this article emphasizes that shame needs to be immediately rooted again, in a constructive direction. This can be achieved through ethics-based political education, electoral system reform, strengthening the role of the media, and implementing strict sanctions.